Exploring cultural patterns in business communication. insights from Europe and Asia - Oana Ursu; Elena Ciortescu (CES Working Papers, 2021)
This paper starts from the assumption that in our current world, dominated by fast-paced changes, culture has acquired increasing prominence, which is likely to affect interpersonal and business relationships alike. Therefore, relying on a number of cultural patterns (high and low context cultures, collaborative and individual cultures and polychronic and monochronic cultures (Hall, 1990, 1997; Moll, 2012), we aim to provide an overview of the dynamics of cultural differences and similarities between Europe and Asia, with a focus on the business environment. Thus, arguing language proficiency does not necessarily ensure successful (business) interaction, we will be analysing a number of elements involved in business communication (e.g. the way in which individuals in a particular culture relate to time or how they position themselves within a group). More precisely, we will be looking into the ways in which people think, negotiate, and manage conflict, in an attempt to identify the various elements that drive specific behaviours and account for cultural expectations and assumptions.
Keywords: 330; cultural patterns; high & low context; collaborative & individual; polychronic and monochronic; Europe vs. Asia